A NEW STAGE OF PENSION REFORM IN RUSSIA: INCREASING PRIVATE PENSIONS - Arkady K. Solovyev (Финансы: теория и практика, 2017)
Article Retracted.A new stage of the pension reform in Russia scheduled for 2015 will be an extension of parametric and institutional reforms aimed at the restructuring of the economic and social system of the country to further adapt it to market conditions. The main areas of the reform are determined by the strategy for long-term development of the pension system of the Russian Federation2 (hereinafter — the Strategy) which substantially amended all prior regulations on mandatory pension insurance (MPI). At the same time, the Strategy remains committed to the transition of the pension system to insurance principles and concepts. In line with the Strategy, the article analyzes the goals and objectives as well as key areas and measures to reform the Russian pension system; explores the institutional and parametric changes planned for the various stages of the reform and sketches the possible solutions in the interests of all the participants of the pension system.